2013
DOI: 10.1002/eji.201242997
|View full text |Cite
|
Sign up to set email alerts
|

CRIg signals induce anti‐intracellular bacterial phagosome activity in a chloride intracellular channel 3‐dependent manner

Abstract: Macrophages provide a first line of defense against bacterial infection by engulfing and killing invading bacteria, but intracellular bacteria such as Listeria monocytogenes (LM) can survive in macrophages by various mechanisms of evasion. Complement receptor of the immunoglobulin (CRIg), a C3b receptor, binds to C3b on opsonized bacteria and facilitates clearance of the bacteria by promoting their uptake. We found that CRIg signaling induced by agonistic anti-CRIg mAb enhanced the killing of intracellular LM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…We also showed that transgenic expression of VSIG4 in cells of the nonphagocytic HeLa cell line cells allows them to take up opsonized LM and selectively target autophagosomes to LM. Our findings demonstrate that VSIG4 signals provide 2 defense mechanisms against intracellular bacterial infections: 1) phagosome-dependent defense involving uptake of the circulating complement-opsonized pathogens and rapid acidification of the phagosomes, as previously reported, 20 and 2) xenophagy-dependent defense by selectively inducing autophagosomes directed against LM that have escaped from phagosomes.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…We also showed that transgenic expression of VSIG4 in cells of the nonphagocytic HeLa cell line cells allows them to take up opsonized LM and selectively target autophagosomes to LM. Our findings demonstrate that VSIG4 signals provide 2 defense mechanisms against intracellular bacterial infections: 1) phagosome-dependent defense involving uptake of the circulating complement-opsonized pathogens and rapid acidification of the phagosomes, as previously reported, 20 and 2) xenophagy-dependent defense by selectively inducing autophagosomes directed against LM that have escaped from phagosomes.…”
Section: Discussionsupporting
confidence: 82%
“…6 Since we treated J774 cells with anti-VSIG4 mAb 1 h after infection with LM, 20 we suspected that many of the phagocytosed LM would already have escaped to the cytosol. Since nevertheless the anti-VSIG4 mAb suppressed LM growth, 20 this implied that VSIG4 triggering also eliminated the escaped LM.…”
Section: Agonistic Anti-vsig4 Antibody Induces Autophagosome Formationmentioning
confidence: 99%
See 3 more Smart Citations